Temel fizik kanunlarının trafik kurallarına uygulanması ile ilgili öğrenci görüşlerinin incelenmesi - Zeyrek, Merve (My University, 2003)
In this study it has been investigated whether students use concepts that they were learned in Impulse - Momentum unit in secondary school in their daily life against the problems about traffic or not, and which misconceptions occur while they interpret as. The problem in this study is, if any conceptual changes happen in students while studying Impulse - Momentum unit with Interactive Screen Transfer Method, Semi Structured Interview Method and Constructivist Teaching Approach. This study has 3 chapters. In first chapter, open-ended questions to determine students' misconceptions in Impulse- Momentum unit have been applied to 243 students in 10th class. In second chapter of study inductive analysis applied pre-tests have been evaluated with inductive analysis method and students acquired way of thinkings related categories have been created. In third chapter of study, using the results of second chapter voluntary, students group have been determined for semi-structured interview and 3 working group 3 in each have been formed. To complete this study's specific analysis a semi-structured interview protocol has been prepared. A discussion platform with using an interactive screen transfer method to convey what exactly students think has been formed. Results of this study show us that how useful making interview and interactive screen transfer on students for revealing misconceptions and shows how it causes conceptual changes in students nature. Also results of this study, interview and interactive screen transfer to students, is successful removing misconceptions in four questions of pre-test, but we can't see same success in remaining 6 questions At the same time diagnosis of this study show us, an hour interview and computer animations that used in interview is not enough to change students' concepts. In this study, semi-structured interview technique found useful in revealing students opinions and in understanding whether any effect on conceptual changing or not. In conclusion, it can be said that students are forced in accepting new knowledges and applying them. According to structured education approach students' opinions are important before coming to physics lessons. Before they take physics lessons, finding which misconceptions and healing physics lessons to annihilate or reduce these misconceptions are all important for increasing students' success.
Keywords: Fizik